Interval type-2 Fuzzy ARAS method for recycling facility location problems - Karagöz, Selman; Deveci, Muhammet; Simic, Vladimir; Aydin, Nezir (Applied soft computing, 2021)
The management of end-of-life vehicles (ELVs) is currently one of the most important ecological topics. The recycling process has essential importance for the environmental and economic sustainability of the ELV management. Istanbul has the highest rate of car ownership population in Turkey as well as an old vehicle fleet. There is a strong motivation to open an additional ELV recycling facility in this mega-city. Facility location is one of the crucial strategic problems for decision-makers. Addressing multi-criteria and highly uncertain nature of the ELV recycling facility location problem, this paper introduces a novel approach to support the facility location process. For the first time, an extension of the Additive ratio assessment (ARAS) method under the interval type-2 fuzzy environment is presented. The novel method is utilized for solving the ELV recycling facility location problem. The potentials and applicability of the presented interval type-2 fuzzy ARAS method are demonstrated throughout the real-life case study of Istanbul. The comparison with the available state-of-the-art interval type-2 fuzzy set based MCDM methods approves its validity and consistency. •An extension of the ARAS method under the interval type-2 fuzzy environment is presented.•The developed IT2F ARAS method is used to evaluate ELV recycling facility locations.•For the first time the ARAS method is applied in the waste management area.•A real-life case study of Istanbul is provided to illustrate the presented method.•The developed IT2F ARAS method can be applied to many other MCDM problems.